1996
DOI: 10.1002/(sici)1097-4644(19960401)61:1<118::aid-jcb13>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of subunit transcript and protein levels on formation of a mitochondrial multienzyme complex

Abstract: Constitutive expression of nuclear genes encoding mitochondrial proteins raises the question of whether these proteins are present in similar amounts in mitochondria of different tissues. We report that amounts of a single multienzyme complex can vary on a per mitochondrion basis depending on the number of mitochondria per cell. Human branched-chain a-keto acid dehydrogenase (BCKD) expression is used as a paradigm in these studies. Expression is compared and contrasted in HepG2 and DG75 cells in which mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Because the active form of El is a tetramer of 2cr and 2~subunits, the data suggest that net complex activity in astrocyte cultures may be limited by availability of the El~subunit. McConnell et al (1996) have also reported that levels of thes ubunit can limit BCKD complex activity. Other known regulatory factors include phosphorylation state regulated by the BCKD kinase (Harris et al, 1986) and product inhibition (acyl-CoA intermediates and NADH).…”
Section: Bcaa and Bcka Metabolism In Primary Rat Brain Cell Culturesmentioning
confidence: 97%
“…Because the active form of El is a tetramer of 2cr and 2~subunits, the data suggest that net complex activity in astrocyte cultures may be limited by availability of the El~subunit. McConnell et al (1996) have also reported that levels of thes ubunit can limit BCKD complex activity. Other known regulatory factors include phosphorylation state regulated by the BCKD kinase (Harris et al, 1986) and product inhibition (acyl-CoA intermediates and NADH).…”
Section: Bcaa and Bcka Metabolism In Primary Rat Brain Cell Culturesmentioning
confidence: 97%
“…Available data suggest that the import of E1β can alter the amount of E1 subunits within a mitochondrion (46,72,73). Likewise, insulin appears to influence the production of E1α which could help to determine the amount of E1 present at any one time and glucocorticoids have been shown to alter E2 and E1β concentration (74).…”
Section: Molecular Genetics Of Bckdmentioning
confidence: 99%